2013
DOI: 10.1371/journal.pone.0074367
|View full text |Cite|
|
Sign up to set email alerts
|

Quantification of Anti-Aggregation Activity of Chaperones: A Test-System Based on Dithiothreitol-Induced Aggregation of Bovine Serum Albumin

Abstract: The methodology for quantification of the anti-aggregation activity of protein and chemical chaperones has been elaborated. The applicability of this methodology was demonstrated using a test-system based on dithiothreitol-induced aggregation of bovine serum albumin at 45°C as an example. Methods for calculating the initial rate of bovine serum albumin aggregation (v agg) have been discussed. The comparison of the dependences of v agg on concentrations of intact and cross-linked α-crystallin allowed us to make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 96 publications
1
22
0
Order By: Relevance
“…For several proteins the unfolding process can be initiated by the cleavage of S S bonds in the protein molecule. Dithiothreitol (DTT)-induced aggregation was demonstrated, for example, for ␣-lactalbumin, insulin, lysozyme and bovine serum albumin [1][2][3][4]. The study of the kinetics of DTT-induced aggregation of ␣-lactalbumin and insulin showed that the formation of start aggregates including the hundreds of molecules of denatured protein occurred at the initial stages of aggregation [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For several proteins the unfolding process can be initiated by the cleavage of S S bonds in the protein molecule. Dithiothreitol (DTT)-induced aggregation was demonstrated, for example, for ␣-lactalbumin, insulin, lysozyme and bovine serum albumin [1][2][3][4]. The study of the kinetics of DTT-induced aggregation of ␣-lactalbumin and insulin showed that the formation of start aggregates including the hundreds of molecules of denatured protein occurred at the initial stages of aggregation [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…One can assume that after the passing the point of intersection ( x > 2.5) the AC of crosslinked α‐crystallin becomes higher than that for intact α‐crystallin. When studying the effect of crosslinking on the chaperone‐like activity of α‐crystallin with the test system based on dithiothreitol‐induced aggregation of bovine serum albumin (BSA), we used the same preparation of crosslinked α‐crystallin. The dependence of the relative rate of aggregation v / v 0 on the [α‐crystallin]/[BSA] ratio was linear demonstrating the decrease in the chaperone‐like activity of α‐crystallin as a result of crosslinking.…”
Section: Discussionmentioning
confidence: 99%
“…Concentration of α‐crystallin was determined spectrophotometrically at 280 nm using the absorption coefficient Acm 1% of 8.5 . Crosslinking α‐crystallin was carried out with glutaraldehyde as a crosslinking agent as described in work of Borzova et al The data of electrophoresis in 12.5% PAGE in the presence of sodium dodecylsulfate and DTT are indicative of complete crosslinking of subunits in the α‐crystallin particles . According to the data on dynamic light scattering the average values of the hydrodynamic radius of intact and crosslinked α‐crystallin were found to be 12.5 and 16.7 nm, respectively .…”
Section: Methodsmentioning
confidence: 99%
“…In principle, chaperones could associate with any, or all, of these species along the amyloidogenesis pathway. A wide range of biophysical techniques including light scattering, changes in fluorescence of histological dyes, circular dichroism, size exclusion chromatography, ultracentrifugation, native mass spectrometry, small-angle X-ray scattering, and nuclear magnetic resonance (NMR) spectroscopy have been employed to determine features of this process 5,10,[15][16][17][18][19][20][21][22][23][24][25] . Significant insights into how proteins aggregate, and how chaperones attenuate aggregation, have been obtained by relating such data to analytical equations in specific regimes [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%